GSM Module in Remote Electrical Loads Control - Blessed Olalekan, Oyebola; Toluwani, Odueso Victor (Asian Journal of Electrical Sciences, 2017)
Electrical appliances power consumption tends to grow in proportion to the increase in the number of large-sized electric home appliances.These Projects describes the technology associated with the Remote Control of Electrical Loads Using GGSM Module. Using GSM networks, a control system has been projected that will act as an embedded system which can control appliances and other devices locally using built-in input and output peripherals. Also the system allow the user to effectively control house or office appliances and equipment via the mobile phone set by sending commands in the form of SMS messages and receiving the appliances status. The main conception behind this project is receiving a coded SMS to trigger or switch home electrical appliances through communication between GSM module and a microcontroller switching circuit.